OPENNESS AND TRANSPARENCY OF DATA ON THE DEVELOPMENT OF LARGE EUROPEAN CITIES - Zablodska, Daria (European Science, 2023)
The article explores the concept of openness and transparency of data on the development of countries, regions, cities, etc. It has been established that there are organizations in the world engaged in evaluating the openness of government data, among whi